Left ventricular mass of persistent masked hypertension in Hong Kong Chinese adolescents: a 4-year follow-up study. (22nd April 2018) - Yam, Man-Ching; So, Hung-Kwan; Kwok, Sit-Yee; Lo, Fung-Cheung; Mok, Chi-Fung; Leung, Chuk-Kwan; Yip, Wai-Kwok; Sung, Yn-Tz
Abstract: Objective: In our previous study, the prevalence of childhood masked hypertension was 11%. This study aims to assess the left ventricular mass index of persistent masked hypertension and determine the factors of elevated left ventricular mass index in Hong Kong Chinese adolescents from a community cohort. Design: Community prospective cohort study, follow-up of a case-control study in community. Subjects: Patients with masked hypertension at baseline were invited to recheck ambulatory blood pressure for the persistence of masked hypertension. Results: A total of 144 out of 165 patients with masked hypertension in the 2011/2012 ambulatory blood pressure survey consented to participate in the study. In all, 48 patients were found to have persistent masked hypertension by ambulatory blood pressure rechecking and were matched with normotensive controls by sex, age, and body height. The left ventricular mass (117.3±39.9 g versus 87.0±28.2 g versus 102.0±28.2 g) and left ventricular mass index (30.1±8.4 g/m 2.7 versus 23.9±6.3 g/m 2.7 versus 25.1±5.7 g/m 2.7 ) were significantly higher in the persistent masked hypertension group (p<0.0001) compared with the patients without persistent masked hypertension and controls. In multivariate linear regression analysis, left ventricular mass index was found to be higher in male gender (β=4.874, p<0.0001) and the patients with persistent masked hypertension (β=2.796, p=0.003). In addition, left ventricular mass index was positively associated with body mass index z-score (β=3.045, p<0.0001) and low-density lipoprotein cholesterol concentration (β=1.634, p=0.015). Conclusions: Persistent masked hypertension in adolescents is associated with elevated left ventricular mass index.